Kinetic limitations in the Mg-Si-H system - Paskevicius, Mark; Sheppard, Drew; Chaudhary, A.; Webb, C.; Gray, E.; Tian, Hu-Yong; Peterson, V.; Buckley, Craig (Elsevier Ltd, 2011)
Magnesium silicide (Mg2Si) has attracted interest as a hydrogen storage material due to favorable thermodynamics (ΔHdesorption = 36 kJ/mol H2) for room temperature operation. To date, direct hydriding of Mg2Si under hydrogen gas to form MgH2 and Si has only been attempted at low pressure and has been hindered by poor kinetics of absorption. In this paper we study the dehydrogenation reaction with in-situ neutron powder diffraction and present results of our attempts to hydrogenate Mg2Si under both hydrogen and deuterium gas up to temperatures of 350 °C and pressures of 1850 bar. Even under these extreme absorption conditions Mg2Si does not absorb any measureable quantity of hydrogen or deuterium.